Audit Tata Kelola Sistem Informasi Keuangan Daerah SIKD Menggunakan IT Framework COBIT 5.0 (Studi Kasus Pada BKAD Kabupaten Bandung Barat) : Audit of regional financial information system governance SIKD using IT Framework Cobit 5.0 - Ahadiansyah, Ramdan; Surya, Rendra Trisyanto (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The stipulation of Permendagri Number 70 of 2019 concerning Regional Government Information Systems is the legal basis for each Regional Apparatus Organization to be obliged to provide regional government and regional finance information through one integrated system, namely SIPD. BKAD West Bandung Regency has implemented the SIKD system in early 2021 as a system, administers, that documents, and processes regional financial management data and other related data information presented to the public. The information system audit in this study was carried out using the COBIT 5 framework by selecting key IT processes in all EDM, APO, BAI, DSS, and MEA domains. The results showed that the maturity of the Regional Financial Information System was at level 2 with the